Smart Building Management Systems and Internet of Things - Jean Yves Astier; Igor Yurievich Zhukov; Oleg Nikolaevich Murashov (Безопасность информационных технологий, 2017)
After a brief historical reminder on SCADA systems, we will present the new challenges regarding modern building technical management (BTM) systems. We identify the technological evolutions, which allow us to address these new issues, and describe the software and hardware architectures of our Building Management Internet of Things (BMIoT) solution. We end by comparing with other older solutions and by a short description of the new business models, our solution allows.